Collaboration Dichotomies In Knowledge Management Success - Jadoon, Immad Khan; Hasnu, Syed Amjad Farid (Journal of Knowledge Management Practice, 2009)
Knowledge management is a not just computer or IT focused concept rather it has a whole gamut of other parameters as well. Information technology does not in itself create knowledge or guarantee knowledge creation but depends on cultural cognition and intra-community interaction. The purpose of this study was to expand the base of knowledge in the area; and empirically test the relationship between intra-community social interaction within an organization and the success of knowledge management system. Methodology used to measure directionality and relationship was correlation. The results of the study indicate that there is a significant positive relationship between collaboration and knowledge management systems and their success.